Research on the Protective Behavior of High Solid Content Epoxy Anti-Corrosive Coating/Aluminum Alloy System in Simulated Ultra-Deep Sea High-Pressure Environment#br# - TANG Chu-tian, LI Xiang, WANG Xi-ming, GUAN Jin-sheng, JIANG Jiong, YANG Jin-song, SUN Li-san, MAO Fei-xiong, LIU Shuan (Cailiao Baohu, 2021)
With the aim of improving the protective performance of aluminum alloy in deep sea environment,a high solid content epoxy anti-corrosive coating for deep sea protection of aluminum alloy was developed.The electrochemical test technology,salt spray accelerated test and coating morphology analysis were used to study the protective behavior of the high solid content epoxy anti-corrosive coating on aluminum alloy at atmospheric pressure and in a simulated ultra-deep sea high-pressure environment(36.0 MPa sea water pressure).Results showed that the salt spray life of the high solid content epoxy anti-corrosive coating on the substrate of aluminum alloy was over 1000 h,and the pull-out adhesion of the coating on aluminum alloy was 11.28~13.52 MPa.After soaking in 36.0 MPa high pressure brine for 35 d,the wet adhesion of the coating was 7.52~8.12 MPa.In the ultra-deep sea high-pressure environment,the film water absorption of aluminum alloy/coating system resulted in the decrease of coating resistance and the increase of capacitance.After 35 days of immersion,the low-frequency impedance mode value of the coating was reduced to 3.85×106Ω·cm2.Furthermore,the pigments and fillers in the coating were loose in deep sea high-pressure environment,which was easy to form a corrosion channel and resulted in coating damage and matrix corrosion.Thus,improving the wet adhesion and compactness of the coating on the metal was the key factor to effectively prolong the protective life of the coating in the deep sea environment.